2008
DOI: 10.1016/j.bbmt.2008.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Does the Hematopoietic Cell Transplantation Specific Comorbidity Index Predict Transplant Outcomes? A Validation Study in a Large Cohort of Umbilical Cord Blood and Matched Related Donor Transplants

Abstract: The hematopoietic cell transplantation specific comorbidity index (HCT-CI) has been recently proposed to predict the probability of nonrelapse mortality (NRM) and overall survival (OS) in allogeneic HCT recipients while taking into account any pretransplant comorbidity. We tested the validity of the HCT-CI in a cohort of 373 adult HCT recipients (184 matched-related donor and 189 unrelated umbilical cord blood) who received a myeloablative (N = 150) or nonmyeloablative (N = 223) conditioning regimen. HCT-CI sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 16 publications
3
48
0
Order By: Relevance
“…[15][16][17][18] These comorbidity scores, such as haemopoietic progenitor cell transplantation (HCT)-comorbidity index (CI), have been validated in some studies to be useful in predicting NRM in transplant candidates in the setting of myeloablative compared with non-myeloablative transplants, albeit in a heterogenous group of patients receiving myeloablative and non-myeloablative TBI-based conditioning regimens. 15,18,19 In others, it was not found to be predictive of mortality on its own in HCT. 20,21 Patients having RIC allografts are, however, very heterogeneous as far as degree of comorbidity is concerned, and it is unclear whether these comorbidity scores can further delineate groups of RIC allograft recipients who will have significantly different NRM and survival.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] These comorbidity scores, such as haemopoietic progenitor cell transplantation (HCT)-comorbidity index (CI), have been validated in some studies to be useful in predicting NRM in transplant candidates in the setting of myeloablative compared with non-myeloablative transplants, albeit in a heterogenous group of patients receiving myeloablative and non-myeloablative TBI-based conditioning regimens. 15,18,19 In others, it was not found to be predictive of mortality on its own in HCT. 20,21 Patients having RIC allografts are, however, very heterogeneous as far as degree of comorbidity is concerned, and it is unclear whether these comorbidity scores can further delineate groups of RIC allograft recipients who will have significantly different NRM and survival.…”
Section: Introductionmentioning
confidence: 99%
“…10 In umbilical cord transplant registry data, HCT-CI did not consistently predict TRM or OS. 11 Similarly, in patients with nonHodgkin's lymphoma conditioned with fludarabine and CY, there was no association between HCT-CI and TRM or OS. 12 Several investigators have reported that although HCT-CI may be useful, it lacks the sensitivity to predict outcome as stratified by the three original groups described.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, PAM score is a global risk assessment score including variable factors of comorbidity, condition of transplantation, and disease risk. The usefulness of these risk assessment scores has been validated by some previous studies [3][4][5][6][7][8][9][10][11][12][13], but the scores failed to predict mortality in other reports [14][15][16].…”
Section: Introductionmentioning
confidence: 94%